2017
DOI: 10.1002/ieam.1881
|View full text |Cite
|
Sign up to set email alerts
|

A review of ecological risk assessment methods for amphibians: Comparative assessment of testing methodologies and available data

Abstract: Historically, ecological risk assessments have rarely included amphibian species, focusing preferentially on other aquatic (fish, invertebrates, algae) and terrestrial wildlife (birds and mammal) species. Often this lack of consideration is due to a paucity of toxicity data, significant variation in study design, uncertainty with regard to exposure, or a combination of all three. Productive risk assessments for amphibians are particularly challenging, given variations in complex life history strategies. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 72 publications
0
21
0
1
Order By: Relevance
“…In particular, for the 96‐hour acute experiments, we used a GLMM with a binomial distribution and logit link function (R package lme4; Bates, Maechler, Bolker, & Walker, ) to evaluate the effects of solvent treatment on the survival and occurrence of abnormalities. We then determined if solvent treatment influenced interorbital distance and mouth size using GLMM with a Gaussian distribution and log link function, including survival as a fixed effect to account for density effects (Johnson et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, for the 96‐hour acute experiments, we used a GLMM with a binomial distribution and logit link function (R package lme4; Bates, Maechler, Bolker, & Walker, ) to evaluate the effects of solvent treatment on the survival and occurrence of abnormalities. We then determined if solvent treatment influenced interorbital distance and mouth size using GLMM with a Gaussian distribution and log link function, including survival as a fixed effect to account for density effects (Johnson et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we used a GLMM with a binomial distribution and logit link function (R package lme4; Bates et al, ) to evaluate solvent effects on the proportion of females to males. For the remaining traits, we included survival as a fixed effect (Johnson et al, ), and used a GLMM with log link (to prevent negative terms in the model; R packages lme4 (Bates et al, ) and lmerTest (Kuznetsova, Brockhoff, & Haubo Bojesen, ) and Gaussian distribution. For GS (considered count data), overdispersion was detected (dispersion value >1; Zuur, Hilbe, & Ieno, ) and was corrected by re‐fitting the model with a Poisson distribution with the glmmPQL function from the MASS package (Venables & Ripley, ) in R (reduced dispersion to 1.01).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphibians appear to be an important test species for HPT axis interactions. Johnson et al (2017) stated that data for long‐term exposures and metamorphosis suggest that amphibians are more sensitive than fish and other vertebrates to compounds that affect the HPT axis, citing Kerby et al (2010) and Veldhoen et al (2006). Veldhoen et al (2006) found that triclosan altered thyroid hormone–associated gene expression, increased hindlimb development, and decreased total body weight.…”
Section: Biological Read‐across For Eatsmentioning
confidence: 99%
“…Because of their varied habitat, life‐histories, and vulnerability to multiple environmental stressors, assessment of chemical risk to amphibians should be placed in a larger, ecologically relevant context (Johnson et al ). Amphibian life cycle and ontogeny are distinct from other taxonomic classes and vary widely between orders.…”
Section: Introductionmentioning
confidence: 99%